Insight into the role of multiple signaling pathways in regulating cancer stem cells of gynecologic cancers. (October 2022) - Song, Yizuo; Pan, Shuya; Li, Kehan; Chen, Xin; Wang, Z. Peter; Zhu, Xueqiong
Abstract: Mounting evidence has demonstrated that a myriad of developmental signaling pathways, such as the Wnt, Notch, Hedgehog and Hippo, are frequently deregulated and play a critical role in regulating cancer stem cell (CSC) activity in human cancers, including gynecologic malignancies. In this review article, we describe an overview of various signaling pathways in human cancers. We further discuss the developmental roles how these pathways regulate CSCs from experimental evidences in gynecologic cancers. Moreover, we mention several compounds targeting CSCs in gynecologic cancers to enhance the treatment outcomes. Therefore, these signaling pathways might be the potential targets for developing targeted therapy in gynecologic cancers.